Streptomyces sp. MUM212 as a Source of Antioxidants with Radical Scavenging and Metal Chelating Properties - Tan, Loh Teng-Hern; Chan, Kok-Gan; Khan, Tahir Mehmood; Bukhari, Sarah Ibrahim; Saokaew, Surasak; Duangjai, Acharaporn; Pusparajah, Priyia; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2017)
Reactive oxygen species and other radicals potentially cause oxidative damage to proteins, lipids and DNA which may ultimately lead to various complications including mutations, carcinogenesis, neurodegeneration, cardiovascular disease, aging and inflammatory disease. Recent reports demonstrate that Streptomyces bacteria produce metabolites with potent antioxidant activity that may be developed into therapeutic drugs to combat oxidative stress. This study shows that Streptomyces sp. MUM212 which was isolated from mangrove soil in Kuala Selangor, Malaysia, could be a potential source of antioxidants. Strain MUM212 was characterized and determined as belonging to the genus Streptomyces using 16S rRNA gene phylogenetic analysis. The MUM212 extract demonstrated significant antioxidant activity through DPPH, ABTS and superoxide radical scavenging assays and also metal-chelating activity of 22.03±3.01%, 61.52±3.13%, 37.47±1.79% and 41.98±0.73% at 4mg/mL, respectively. Moreover, MUM212 extract was demonstrated to inhibit lipid peroxidation up to 16.72±2.64% at 4 mg/mL and restore survival of Vero cells from H2O2-induced oxidative damages. The antioxidant activities from the MUM212 extract correlated well with its total phenolic contents; and this in turn was in keeping with the GC-MS analysis which revealed the presence of phenolic compounds that could be responsible for the antioxidant properties of the extract. Other chemical constituents detected included hydrocarbons, alcohols and cyclic dipeptides which may have contributed to the overall antioxidant capacity of MUM212 extract. As a whole, strain MUM212 seems to have potential as a promising source of novel molecules for future development of antioxidative therapeutic agents against oxidative stress-related diseases.